2021
DOI: 10.1038/s41598-021-97120-x
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV2 infection: functional and morphological cardiopulmonary changes in elite handball players

Abstract: There is increasing evidence of cardiac involvement post-SARS-CoV-2 infections in symptomatic as well as in oligo- and asymptomatic athletes. This study aimed to characterize the possible early effects of SARS-CoV-2 infections on myocardial morphology and cardiopulmonary function in athletes. Eight male elite handball players (27 ± 3.5 y) with past SARS-CoV-2 infection were compared with four uninfected teammates (22 ± 2.6 y). Infected athletes were examined 19 ± 7 days after the first positive PCR test. Echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 28 publications
7
48
3
1
Order By: Relevance
“…Specifically, players reduced their match intensity by 4.1% ± 3.5% after COVID-19. These findings confirm and extend the results of Fikenzer and colleagues (Fikenzer et al, 2021), who observed performance impairments in male elite handball players after COVID-19. Additionally, we observed that "general fatigue" and "muscle fatigue" symptoms were perceived by several players (77% and 54%, respectively) even following COVID-19, suggesting that these symptoms may have played a key role in affecting players' performance.…”
Section: Covid-19 and Metabolic Powersupporting
confidence: 92%
See 3 more Smart Citations
“…Specifically, players reduced their match intensity by 4.1% ± 3.5% after COVID-19. These findings confirm and extend the results of Fikenzer and colleagues (Fikenzer et al, 2021), who observed performance impairments in male elite handball players after COVID-19. Additionally, we observed that "general fatigue" and "muscle fatigue" symptoms were perceived by several players (77% and 54%, respectively) even following COVID-19, suggesting that these symptoms may have played a key role in affecting players' performance.…”
Section: Covid-19 and Metabolic Powersupporting
confidence: 92%
“…Fatigue symptoms could be of particular relevance in the process of RTS decision‐making, as they may negatively affect athletes’ performance, as well as increase the risk of injuries and other negative outcomes following COVID‐19. To the best of our knowledge, only one study has ever compared physical performance before and after COVID‐19 in athletes, showing decrements in peak power output during an incremental cardiopulmonary exercise test (Fikenzer et al, 2021 ). Nevertheless, future studies are needed to confirm these results and shed some light on the long‐term COVID‐19 symptoms affecting athletes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, lower peak HR on follow-up CPET is not explained by retraining, and may indicate COVID-19 impact on the autonomic response to exercise as has been suggested by others’ work in the general population 33–36 and one prior longitudinal study in variably symptomatic athletes. 19 Our results identify important directions for future in-depth work aimed at better delineating the relationships among persistent cardiopulmonary symptoms after COVID-19, detraining and retraining, and these exercise testing parameters.…”
Section: Discussionmentioning
confidence: 71%